Long-term management of GERD in the elderly with pantoprazole - Carlo Calabrese (Dove Medical Press, 2007)
Carlo Calabrese, Anna Fabbri, Giulio Di FeboDepartment of Internal Medicine and Gastroenterology, University of Bologna, ItalyAbstract: The prevalence of gastroesophageal reflux disease (GERD) increases with age and elderly are more likely to develop severe disease. Older patients often complain of less severe or frequent heartburn than younger patients and they may present with atypical symptoms such as dysphagia, weight loss, or extraesophageal symptoms. Proton pump inhibitors (PPIs) are central in the management of GERD and are unchallenged with regards to their efficacy. They are considered safe and more effective than histamine receptor antagonists for healing esophagitis and for preventing its recurrence using a long term maintenance treatment. PPI have minimal side effects and few slight drug interactions and are considered safe for long term treatment. Pantoprazole is significantly effective both for acute and long-term treatment with excellent control of relapse and symptoms. It is well tolerated even for long-term therapy and its tolerability is optimal. Pantoprazole shows to have minimal interactions with other drugs because of a lower affinity for cytocrome P450 than older PPIs. Although the majority of elderly has concomitant illnesses and receive other drugs, this does not adversely effect the efficacy of pantoprazole because of its pharmacokinetics, which are independent of patient age. Clinical practice suggests that a low dose maintenance of PPIs should be used in older patients with GERD.Keywords: GERD, long-term management, pantoprazole, safety, efficacy, tolerability